(untitled) - James, L Gould (New York, 1996)
The book combines biochemistry, cell biology, microbiology, batany, zoology, and ecology into a single intyegrated text. In Part I, the book discusses the chemical and cellular basis of life. Part II includes the perpetuation of life. Part III covers evolutionary biology, including the role of parasites and parasitoids. In Part IV, the book revises the genesis and diversity of organisms. It discusses the biology of organisms in part V. Finally, in Part VI, the book deals with ecology, including the law of constant yield
Keywords: Biology